(untitled) (Jurnal Pustaka, 2026)
This research explains how community participation in green open spaces in the city of Padang is used to prevent air pollution. The method used in this research is literature study. The literature study in this research is a series of activities relating to methods of reading and recording objectively, systematically, analytically and critically about green open spaces to prevent air pollution. The main problem discussed is how the community behaves in supporting the provision of Green Open Space (RTH). The aim of this research article is to increase community participation in green open spaces to overcome air pollution. The results of this research show that community participants still lack public awareness of the importance of maintaining green open spaces, as well as a lack of knowledge about preserving the environment. One example of the lack of public awareness is evidenced by warnings not to throw away certain places which have become prohibited by the community and the government.